2021
DOI: 10.15381/rivep.v32i1.19506
|View full text |Cite
|
Sign up to set email alerts
|

Morfometría y subpoblaciones de espermatozoides de llama (Lama glama) usando el sistema ISAS® CASA-Morph

Abstract: El objetivo del estudio fue determinar la existencia de subpoblaciones espermáticas según la morfometría de los espermatozoides de llama, utilizando un sistema CASA-Morph. Se colectó semen de cuatro llamas Q’ara de 4-6 años mediante el método de electroeyaculación en cuatro oportunidades por animal, con intervalos de una semana. Se determinó el volumen, movilidad total, concentración de espermatozoides, porcentaje de espermatozoides vivos y porcentaje de espermatozoides con reacción acrosomal. Los parámetros m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Significant research attention has been focused on documenting and analysing sperm morphometry in several species such as fox (Soler, Contell, et al, 2017), boar (Barquero, Soler, et al, 2021), dairy cattle (Valverde et al, 2016), alpaca (Cucho et al, 2019), llama (Cucho, Gallegos, et al, 2021), dog (Soler, Alambiaga, et al, 2017) and vicuña (Cucho, Puelles, et al, 2021). It has been reported that relevant variability exists in sperm morphometry among males from the same population (Górski, Kondracki, Strachocka, & Wysokińska, 2017; Górski, Kondracki, & Wysokińska, 2017; Morrow & Gage, 2001) and individual variation within males has also been more recently reported (Maroto‐Morales et al, 2012; Ros‐Santaella et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Significant research attention has been focused on documenting and analysing sperm morphometry in several species such as fox (Soler, Contell, et al, 2017), boar (Barquero, Soler, et al, 2021), dairy cattle (Valverde et al, 2016), alpaca (Cucho et al, 2019), llama (Cucho, Gallegos, et al, 2021), dog (Soler, Alambiaga, et al, 2017) and vicuña (Cucho, Puelles, et al, 2021). It has been reported that relevant variability exists in sperm morphometry among males from the same population (Górski, Kondracki, Strachocka, & Wysokińska, 2017; Górski, Kondracki, & Wysokińska, 2017; Morrow & Gage, 2001) and individual variation within males has also been more recently reported (Maroto‐Morales et al, 2012; Ros‐Santaella et al, 2015).…”
Section: Introductionmentioning
confidence: 99%